Building the Financial Literacy of Elementary School Students: Developing Monopoly Education Teaching Materials - Nurfurqon, Faridillah Fahmi; Fauzi, Muhammad Rizal; Arga, Hana Sakura Putu; Virgiana, Rayan; Sapriya, ‎‎; Agustin, Mubiar (KnE Social Sciences, 2025)
Financial literacy is one of the six literacies agreed upon by the World Economic Forum that must be mastered by teachers and students as an initial means of understanding and managing finances. In addition, financial literacy is related not only to managing finances but also to knowledge and skills in applying one’s experiences to make effective and appropriate decisions. Given this, it is necessary to develop teaching materials that can help students understand the urgency of financial literacy, so that it can not only provide them with short-term benefits but also give them a strong foundation for a more stable and sustainable financial future. Financial literacy learning for elementary school students is important and a valuable investment for their financial future. The purpose of this study is to develop Monopoly Education Teaching Materials (MOLEK): Building Elementary School Students’ Financial Literacy. To achieve these goals, this study used research and development model with the following steps: 1) research and information collection 2) planning 3) initial product development and 4) initial trial 5) initial product revision 6) field trial 7) product revision 8) validation and field trial 9) final product revision 10) dissemination and implementation. The result of this study is the creation of the MOLEK, which has been tested and published in an accredited national journal.